PENGEMBANGAN LEMBAR KEGIATAN PESERTA DIDIK (LKPD) BERBASIS KONSTRUKTIVISME PADA POKOK BAHASAN LAJU REAKSI - Erlita, Dina; M. Noer, Asmadi; Haryati, Sri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The objective of this research is to develop the student’s work sheet on the subject of reaction rate.The research is done in FKIP Riau University. The method of this research is design reserach with the 4-D model which include Define, Design, Develop, and Disseminate. But this research is done until develop. The data research is validation’s result of student work sheet based on constructivism on reaction rate. The data analysis technique is descriptive statistic analysis and analysis done by percentage of validation score. The average scores of valuation by validator’s team from four expendiency components such as content, language, layout, and graphical are 92,86%, 93,33%, 95,83%, and 93,75%. In spite of average score totally of student worksheet based on contructisvism on reaction rate is 93,94% which is valid criteria. It means means student work sheet that is developed ready to use. Whereas percentage response of students is 95,75% to very good criteria.Key Words: Student Work Sheet, Constructivism, and Reaction Rate.